Female masculinity - Halberstam, Jack, 1961- (Duke University Press, 1998)
Through detailed textual readings as well as empirical research, Halberstam uncovers a hidden history of female masculinities while arguing for a more nuanced understanding of gender categories that would incorporate rather than pathologize them. She also explores issues of transsexuality among 'transgender dykes' - lesbians who pass as men - and female-to-male transsexuals who may find the label of 'lesbian' a temporary refuge. Halberstam also tackles such topics as women and boxing, butches in Hollywood and independent cinema, and the phenomenon of male impersonators. Female Masculinity signals a new understanding of masculine behaviours and identities, and a new direction in interdisciplinary queer scholarship